Interoperable web sharing of environmental models using OGC web processing service and Open Modeling Interface (OpenMI). (November 2020) - Zhang, Mingda; Jiang, Liangcun; Yue, Peng; Gong, Jianya
Abstract: With the advancement of Web technologies, the service-oriented approach has become increasingly popular to share and couple environmental models. Interoperability is critical to the access and integration of Web services. The OGC Web Processing Service (WPS) defines an interoperable protocol for process execution on the Web. However, it has limitations in supporting time-step calculations that are usually required by complex models, e.g., time marching models. The Open Modeling Interface (OpenMI) standard brings about interoperability for time-step based interactions between modeling components. This paper introduces an approach to sharing environmental models on the Web by coupling OpenMI and WPS. Key issues, including maintaining state, data representation, model description, and model execution, are considered in our approach. An open-source software is developed to support the deployment of the environment models in an interoperable way. TOPMODEL and SWMM5 use cases illustrate the applicability of the approach and implementation. Highlights: This paper proposes an approach to sharing environmental models on the Web by coupling OpenMI and OGC WPS. Key issues including maintaining state, data representation, model description, and model execution are considered. XML schema for WPS extensions and an open-source software for the the deployment of the environment models are provided.